Uthentication of model of dynamics ukrainian fund index of PFTS - Андрієнко, Валентина Михайлівна (Technology audit and production reserves, 2012)
In the article presented results of research of structure of the Ukrainian fund index of PFTS and ground of method of design of his dynamics